BITTER HERBS OF EASTERN NIGERIA (GONGRONEMA LATIFOLIUM, VERNONIA AMYGDALINA AND VITEX DONIANA): A REVIEW - Chinwe U., Asuzu (African Journal of Traditional, Complementary and Alternative Medicines, 2018)
Background: The article is a review of three bitter vegetables consumed in South-eastern Nigeria (Gongronemalatifolium, Vernonia amygdalina and Vitex doniana). These vegetables are not very palatable to taste but are highlyfamed because of the myriad of illnesses that they are reputed to cure and manage. The different aspects of thesevegetables reviewed are their ethnobotany, zoo pharmacology, bioactivity, phytochemistry and toxicity.Materials and method: The literatures consulted were searched using electronic search engines (Google, Googlescholar and Pubmed). Substantial amount of literature was consulted but only those directly related to the main reviewwere selected.Result: The review revealed that the three bitter vegetables possessed phytochemicals like saponins, flavonoids,alkaloids among others that justify the claims of curing and managing many of the illnesses that traditional folksattribute to them. From literature, antimicrobial, antinflammatory, antidiabetic, antioxidant and anti cancer activitieswere attributed to these three bitter herbs. Antinutritional substances like phytate and oxalate reported in these herbswere not regarded as harmful for human consumption because of the traditional method of processing the vegetables bysqueeze washing in several changes of water.Conclusion: The three bitter herbs are regarded as beneficial for human consumption and the information should bedisseminated to a large audience.Key words: V. amygdalina, V. doniana, G.